Quality characteristics of goat milk powder produced by freeze drying followed by UV-C radiation sterilization - Zhezhe Yu; Shangchen Fu; Linqiang Li; Yongfeng Liu (Food Chemistry: X, 2024)
Goat milk was directly freeze-dried into milk powder after freezing and then sterilized using UV-C radiation to produce low-dose, medium-dose and high-dose UV-C radiation sterilized freeze-dried goat milk powder (LGP, MGP and HGP). UV-C sterilization effectively reduced the total bacteria count and coliform bacteria in the goat milk powder while preserving the active proteins, and maintaining the color unchanged. Additionally, LGP, MGP, and HGP all exhibited a moisture content below 5 g/100 g and water activity below 0.5. Upon reconstitution, the milk powder formed uniform and stable emulsion. During accelerated storage tests, the increased Aw did not compromise the microbial quality of milk powder, and there were no significant changes in active proteins as confirmed via SDS-PAGE results. Furthermore, the color parameters (a*, b* and ΔE) showed a strong correlation with hydroxymethyl furfural levels.